Implementasi Desain Pembelajaran Literasi Di SDN Kayumpia, Sigi Dan SDN Lemahduhur, Bogor - Rahmat Hidayat, Asep; Kuswanto; Wicaksono, Dirgantara (Shofanah Media Berkah, 2025)
This study examines the implementation of literacy learning design at SDN Kayumpia, Sigi, and SD N Lemahduhur, Bogor, using a qualitative narrative approach. It aims to understand the context, challenges, and impacts of literacy learning design on students’ skills in these rural schools. Data were collected through in-depth interviews with 4 teachers, 2 principals, and 10 students, classroom observations, and RPP document analysis. Narrative analysis revealed that key needs include culturally relevant reading materials, teacher training in literacy strategies, and integration of local context in learning. Major challenges include limited resources, such as a lack of reading books, and insufficient teacher professional development for cross-curricular literacy integration. However, a local wisdom-based approach, such as using folktales, enhanced student engagement. The findings indicate improved student motivation and reading skills, though implementation is hindered by a rigid curriculum. The study recommends developing contextual literacy resources, ongoing teacher training, and curriculum flexibility to support the School Literacy Movement. This research contributes to the development of relevant literacy practices in rural schools.